Èèkàn dúdú ní ílé imo: o movimento negro, a intelectualidade negra e as instituições orgânicas de não esquecimento - Jessof, Micaela Severo da Fonseca (2025)
This research is an articulation between insurgent school education and organic institutions of non-forgetting. The mobilizing problem of the research was: can organic institutions of non-forgetting and insurgent education resulting from the action of Black Intellectuals and the Black Movement contribute to reorganizing life in the Diaspora? The general objective was to investigate how èèkàn dúdú ní ilẹ́ imọ, that is, black roots, the different spaces of knowledge/knowledge, observing the constitutive processes of strategies to confront the suppression of black memory. The research favored a qualitative approach, based on historical-social processes, assumptions and the holistic capacity of the Afro-descendant Methodology; in the production and analysis of the data, documentary and bibliographic research instruments were used, as well as aspects and dynamics woven by interactions and experiences through oral tradition. Direct and participant observation was used, with recording in a field diary. The work addresses a contextualization of the Brazilian educational space, highlighting colonialism and coloniality in order to understand the insurgent action, investigate the relationship/dynamics between insurgent knowledge, educational space and the potential of terreirized pedagogy; thus, it analyzes the performance of the Black Movement and its Black Intellectuality in the educational environment, especially in the period after the Durban Conference. Finally, the study revealed the importance of organic institutions of non-forgetting, which identify and operate in the preservation of black memory, culture, traits and evidence and can be proponents and drivers in a way that is common to them, as a possible important agent in confronting attempts to erase black memory and, consequently, in the implementation of public educational policies with emancipatory perspectives for black social groups.